Self-sacrificial templating synthesis of self-assembly 3D layered double hydroxide nanosheets using nano-SiO2 under facile conditions. Issue 99 (11th October 2016) - Li, Cunjun; Lu, Hong; Lin, Yinyin; Xie, Xiangli; Wang, Hai; Wang, Linjiang
Abstract : Self-assembly 3D layered double hydroxide (LDH) nanosheets were synthesized using nano-SiO2 as self-sacrificial templates via a facile bottom-up strategy. Abstract : Self-assembly 3D layered double hydroxide (LDH) nanosheets were synthesized using nano-SiO2 as self-sacrificial templates via a facile bottom-up strategy. It is an environmentally friendly and economic strategy to prepare LDH nanosheets in comparison with the conventional method by exfoliation of bulk LDHs.